2019
DOI: 10.1259/bjr.20190056
|View full text |Cite
|
Sign up to set email alerts
|

Reduced motion and improved rectal dosimetry through endorectal immobilization for prostate stereotactic body radiotherapy

Abstract: Dose escalation in prostate cancer radiotherapy has been shown to improve biochemical control in all risk groups. 1 It is estimated that doses as high as 86.5 to 95.5 Gy are required to achieve prostate cancer ablation. 2 Such dose escalation must be balanced against the potential of increased gastrointestinal and genitourinary toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…( 32 ) were interested in the influence of the hydrogel spacer on the intra-fraction motions during irradiation with MRI-LINAC, and it was reported that the pitch rotation decreased significantly due to the use of this strategy. The use of the endorectal balloon or hydrogel spacer in SBRT is a possible option that has shown benefits, particularly in dosimetry ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 32 ) were interested in the influence of the hydrogel spacer on the intra-fraction motions during irradiation with MRI-LINAC, and it was reported that the pitch rotation decreased significantly due to the use of this strategy. The use of the endorectal balloon or hydrogel spacer in SBRT is a possible option that has shown benefits, particularly in dosimetry ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study by Mahdavi et al has been demonstrated that using a rectal retractor during dose-escalated prostate, EBRT not only reduces the posterior rectal wall doses but also it can significantly decrease radiation doses to the anterior rectal wall (15). Furthermore, the rectal retractor can reduce interand intra-fraction prostate motions (42,43). The use of endorectal balloon can also significantly reduce radiation doses to the posterior rectal wall (9).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, radiotherapy combined with capecitabine in rectal cancer patients after neoadjuvant therapy has great advantages [ 19 , 20 ]. In recent years, many scholars have proposed that radiotherapy combined with capecitabine in rectal cancer patients after neoadjuvant therapy can reduce patients' adverse reactions and has a positive effect on improving patients' survival rate [ 21 , 22 ]. In this study, in order to investigate the clinical effect of radiotherapy combined with capecitabine in rectal cancer patients after neoadjuvant therapy, the patients in the control group were treated with radiotherapy, while the patients in the experimental group were treated with radiotherapy combined with capecitabine.…”
Section: Discussionmentioning
confidence: 99%